SUBLIMATION OF INNOVATIVE-INTENTIONAL FACTORS INTO COMPETITIVE ADVANTAGES OF ECONOMIC SYSTEMS - Kubiniy, Nataliya; Misiailo, Oksana; Belei, Nataliia (Current Problems of Sustainable Development, 2026)
The relevance of the topic of research is due to the fact that in the context of globalization, digitalization, and increased international economic competition, it is the level of competitiveness that determines the ability of the economy to ensure sustainable economic growth, increase the well-being of the population, and efficient use of resources. The article has achieved the goal of substantiating the feasibility and necessity of introducing innovative intentional factors into the activities of the economic system and their sublimation into competitive advantages. To achieve the goal, an understanding of the concept of sublimation of factors is presented, the essence of innovative intentional factors is revealed, the conditions for sublimation of factors into competitive advantages are shown, and the imperatives for sublimation of innovative intentional factors into competitive advantages are defined. The article proves that innovative intentional factors are those factors that are predetermined, strategically oriented and act as a result of intentions determined by management. In the context of this study, sublimation is considered as the transformation of internal impulses of the economic system, factors into a certain new qualitative substance, actions or processes. Within the scope of the declared topic and purpose of the scientific work, sublimation is understood as actions that transform factors that are oriented towards active, intelligent innovative activity that forms the competitive advantages of the economic system. Innovative intentional factors are sublimated into competitive advantages in the presence of such conditions as appropriate human potential and proactive management. Synergy, strategic orientation and emergence are highlighted as imperatives of sublimation. It is proved that the innovative activity of the economic system is the result of the complex action of many factors that interact with each other. To increase it and transform it into competitive advantages, it is necessary to form a favorable economic environment, develop human capital, improve the institutional base, modernize infrastructure and stimulate investments. Only a systemic approach to regional development management will ensure sustainable growth and strengthen the region’s position in the conditions of global competition. The concept of sublimation of factors is introduced for the first time, imperatives and conditions are defined. The practical significance lies in the fact that it introduces the resource of intentions into the economy and the tool of intentions in management.